Lost Gear on Blue Swimming Crab Fisheries in Banten Bay: Case of Abandoned, Lost or Discarded Fishing Gear: HILANGNYA ALAT TANGKAP PADA PERIKANAN RAJUNGAN DI TELUK BANTEN: KASUS ABANDONED, LOST OR DISCARDED FISHING GEAR - Susanto, Adi; Syafrie, Hendrawan; Nurdin, Hery Sutrawan; Irnawati, Ririn; Supadminingsih, Fahresa Nugraheni; Hamzah, Asep; Kurniawati, Vaya (Bogor Agricultural University, 2022)
Blue swimming crab is one of the capture fisheries sector leading commodities in Banten Bay which is caught using gill nets and collapsible traps. The risk of lost fishing gears during operation is very high, both due to the bad weather and interactions with other fishing gear. The Abandoned, Lost or Discarded Fishing Gear (ALDFG) contributes significantly to the abundance of marine plactics in the world which has a negative impact on the sustainability of fish resources, water quality and endangers the safety of navigation. Nevertheless, there have been no mitigation activities and efforts to reduce ALDFG in the Banten Bay. This study aims to identify the global causes of lost fishing gear derived from blue swimming crab fisheries in Banten Bay. Data were collected around the Archipelagic Fishing Port (PPN) of Karangantu in May-June 2022. In-depth interviews were conducted with 28 respondents who were selected purposively and the results were analyzed descriptively. The results showed that generally, the causes of lost gear were conflicts with other fishing gear which constitute 64%, whilst human errors during fishing operations and bad weather contributed 19% and 17%, respectively. Keywords: ALDFG, conflict, blue swimming crab, lost gear.